State Policy to Attract Investment Based on Tax Exemption: Economic Analysis of Developing Countries in the 2016-2022 Period - Deivids Reinis Andrias (International Journal of Science and Society, 2023)
This paper is intended to respond to the following questionings: facing national policies dismantling, which focused on regional development and heterogeneity obliteration among the different regions, how much can state tax and financial incentives alter inter-regional labor division and change territorial productive specializations? Do fiscal incentives necessarily change state industrial activity within national production? Do they bear straight relation to the state productive structures’ alterations? The subsidizing data, for the present analysis, illustrate that tax reduction do not necessarily contribute to regional industrial activity decentralization. Furthermore, many of the activities which were favored by the aforementioned incentives and presented spatial decentralization were also influenced, to a considerable extent, by other conditioning circumstances, mainly observed in non-durable consumer goods’ producing activities. This paper aims to show that the Ceará State policy of attraction of companies, since the years 2018-2022, was not capable of modify the participation of the state in the Value of the Industrial Transformation, neither promote significant changes in its productive structure in a way to offer greater diversification and bigger complexity of its industrial structure.